Reflections on HIS 2014: in praise of enthusiasts. Issue 4 (April 2015) - Walker, A.M.
Summary Medical conferences have had a bad press recently. They have been accused of leaving nothing but indifferent research and an enormous carbon footprint. They are also likely to contribute to 'intervention bias' in healthcare, in that the speakers tend to be selected from among the more enthusiastic interventionists and charismatic optimists. But this weakness is arguably also an important strength, for they can be the vehicle by which participants are inspired to innovate and evaluate. It is difficult to predict the outcome of interventions aimed at prevention and control of infection because they involve interactions between people and complex systems, not to mention the invisible agents of infection. Progress therefore depends largely on the empirical approach – trial and error. In this context we need both enthusiasts to inspire trial and sceptics to expose error. Conferences deserve support for encouraging debate between enthusiasts and sceptics, for providing a forum for cross-fertilization between sub-specialties, and for inspiring trainees as well as practitioners. The papers presented in this issue of JHI illustrate the wide range of contemporary challenges in healthcare-associated infection, and summarize the 'state of the art' of infection prevention and control.